Twelve-Month Clinical and Quality-of-Life Outcomes in the Interventional Management of Stroke III Trial. Issue 5 (May 2015) - Palesch, Yuko Y.; Yeatts, Sharon D.; Tomsick, Thomas A.; Foster, Lydia D.; Demchuk, Andrew M.; Khatri, Pooja; Hill, Michael D.; Jauch, Edward C.; Jovin, Tudor G.; Yan, Bernard; von Kummer, Rüdiger; Molina, Carlos A.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Randomized trials have indicated a benefit for endovascular therapy in appropriately selected stroke patients at 3 months, but data regarding outcomes at 12 months are currently lacking. Methods— We compared functional and quality-of-life outcomes at 12 months overall and by stroke severity in stroke patients treated with intravenous tissue-type plasminogen activator followed by endovascular treatment as compared with intravenous tissue-type plasminogen activator alone in the Interventional Management of Stroke III Trial. The key outcome measures were a modified Rankin Scale score ⩽2 (functional independence) and the Euro-QoL EQ-5D, a health-related quality-of-life measure. Results— 656 subjects with moderate-to-severe stroke (National Institutes of Health Stroke Scale ≥8) were enrolled at 58 centers in the United States (41 sites), Canada (7), Australia (4), and Europe (6). There was an interaction between treatment group and stroke severity in the repeated measures analysis of modified Rankin Scale ⩽2 outcome (P=0.039). In the 204 participants with severe stroke (National Institutes of Health Stroke Scale ≥20), a greater proportion of the endovascular group had a modified Rankin Scale ⩽2 (32.5%) at 12 months as compared with the intravenous tissue-type plasminogen activator group (18.6%, P=0.037); no difference was seen for the 452 participants with moderately severe strokes (55.6% versus 57.7%). In participants with severe stroke, the endovascular group had 35.2 (95% confidence interval: 2.1, 73.3) more quality-adjusted-days over 12 months as compared with intravenous tissue-type plasminogen activator alone. Conclusions— Endovascular therapy improves functional outcome and health-related quality-of-life at 12 months after severe ischemic stroke. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00359424.